2015
DOI: 10.1155/2015/389294
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated Tip Catheters for Radiofrequency Ablation in Ventricular Tachycardia

Abstract: Radiofrequency (RF) ablation with irrigated tip catheters decreases the likelihood of thrombus and char formation and enables the creation of larger lesions. Due to the potential dramatic consequences, the prevention of thromboembolic events is of particular importance for left-sided procedures. Although acute success rates of ventricular tachycardia (VT) ablation are satisfactory, recurrence rate is high. Apart from the progress of the underlying disease, reconduction and the lack of effective transmural lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“… 23 26 , 29 33 Patel et al 30 reported on a 262 patient study comparing CA to non-ablative strategies and found the rate of recurrent VT was lower in CA populations than in the non-CA cohort. Numerous other reports have demonstrated the efficacy and potential of CA as a first-line strategy for VT. 23 , 24 , 26 , 31 33 While promising, RF CA is not without issues. Baldinger et al 29 recently analyzed the issues with RF CA in a cardiac setting and found some of the reasons for failed or limited ablation success were a result of limited access, failure to identify target, failure to completely ablate the target, proximity to coronary artery and phrenic nerve, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 26 , 29 33 Patel et al 30 reported on a 262 patient study comparing CA to non-ablative strategies and found the rate of recurrent VT was lower in CA populations than in the non-CA cohort. Numerous other reports have demonstrated the efficacy and potential of CA as a first-line strategy for VT. 23 , 24 , 26 , 31 33 While promising, RF CA is not without issues. Baldinger et al 29 recently analyzed the issues with RF CA in a cardiac setting and found some of the reasons for failed or limited ablation success were a result of limited access, failure to identify target, failure to completely ablate the target, proximity to coronary artery and phrenic nerve, among others.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a major cause of recurrent VT following CA is a result of incomplete ablation (creation of a full thickness transmural lesion) and that a combined endo/epicardial ablation approach is often necessary for VT. 32 While promising, RF CA remains associated with a high degree of recurrence, incidence of damage to adjacent structures (collateral damage), and procedural pain, limiting its widespread use as a first-line treatment. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…2,4 If mechanical perforation occurs, pericardiocentesis is usually sufficient to stop the bleeding. When the tamponade is related to the ablation, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…1 Under certain circumstances, PVCs may initiate ventricular tachycardia (VT), polymorphic VT or ventricular fibrillation, all of which can be the cause of sudden cardiac death. 2 Catheter ablation, in cases of recurrent VT and monomorphic focal PVCs, is the method of choice for the management of arrhythmia. 3 The ablation success rate of VT and PVC is between 60 to 90%, with low complication rates.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the indirect transmission of the RF current into the tissue through the irrigation saline solution, image artefacts associated with light absorption by metallic components or acoustic reflections at the catheter tip can be avoided. Active cooling provided by irrigated catheters is in fact an established method implemented in clinical cardiac RF ablation procedures that has been shown to increase efficiency of the lesion generation and reduce the risk of tissue charring and steam pops [28]. In the ex-vivo porcine heart ablation experiments different chambers of the heart were successfully ablated providing uniform coagulum without any tissue charring, while the OA signal variations associated with the temperature increase and chemical transformations during coagulation could be monitored in real-time.…”
Section: Radiofrequency (Rf) Catheter Ablation Is Widely Employed Formentioning
confidence: 99%